The Discourse of Voicemail - Mishler, Alan (HERMES - Journal of Language and Communication in Business, 2008)
This paper attempts to determine to what degree voicemail messages can be considered a discourse genre – that is, to what degree and in what ways they appear to be uniform across speakers. Thirty-seven voice messages were recorded from the cellular phones of three University of Michigan students. The messages were analyzed in terms of their overall structure, the discursive functions that were executed therein, and the speciﬁc words, phrases and prosodic strategies that were used to execute certain functions. The messages were found to have highly uniform openings and closings, and the message bodies were found to reduce to a small set of discursive functions. In addition, certain words, phrases and devices appeared frequently and in predictable locations within the messages. It is concluded that voicemail message-leaving is a highly structured act governed by conventions that arise both from face-to-face conversation and from the speciﬁc constraints of the medium.